2013
DOI: 10.1093/jb/mvt024
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of syndecan-4 upregulation by TNF-  in the endothelium-like EAhy926 cells

Abstract: Syndecan-4, a cell-surface heparan sulfate proteoglycan, can participate in inflammation and wound healing as a host defense molecule. Tumour necrosis factor (TNF)-α, one of the most potent proinflammatory cytokines, is known to upregulate syndecan-4 expression, but the precise mechanisms are unclear. To elucidate these mechanisms in detail, we examined syndecan-4 upregulation by TNF-α in the endothelium-like EAhy926 cell. Of the two putative nuclear factor kappa-B (NF-κB) binding sites in the syndecan-4 gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 30 publications
2
14
0
1
Order By: Relevance
“…We previously reported that in the NP inflammatory cytokines, TNF‐α and IL‐1β regulate expression of SDC4 through NF‐κB signaling (18). Our studies showed that p65/RelA interacts with a conserved κB element located at –97/–88 bp in SDC4 promoter in NP cells, resulting in increased gene expression, an observation also confirmed in endothelium‐like cells very recently (19). Notably, our work showed that SDC4, through its HS chains, promotes Agc1 degradation by enhancing post‐translational processing of a disintegrin‐like and metalloprotease with thrombospondin type I motifs 5 (ADAMTS‐5) protein, likely playing a key role in pathogenesis of disc disease (18).…”
supporting
confidence: 83%
“…We previously reported that in the NP inflammatory cytokines, TNF‐α and IL‐1β regulate expression of SDC4 through NF‐κB signaling (18). Our studies showed that p65/RelA interacts with a conserved κB element located at –97/–88 bp in SDC4 promoter in NP cells, resulting in increased gene expression, an observation also confirmed in endothelium‐like cells very recently (19). Notably, our work showed that SDC4, through its HS chains, promotes Agc1 degradation by enhancing post‐translational processing of a disintegrin‐like and metalloprotease with thrombospondin type I motifs 5 (ADAMTS‐5) protein, likely playing a key role in pathogenesis of disc disease (18).…”
supporting
confidence: 83%
“…Although little is known about the regulation of syndecan-4 synthesis, studies confirmed its increased expression in vascular smooth muscle cells [27] and osteoblasts [28] and decreased expression in satellite cells [29] following exposure to FGF-2. Furthermore, in vascular endothelial cells, tumor necrosis factor-α [30,31], lipopolysaccharide, and interleukin-1β [25] induce syndecan-4 expression; however, the signaling pathways that mediate syndecan-4 expression remained unclear. Recently, it was reported that the HIF-1-PHD2 axis upregulates syndecan-4 expression in cultured nucleus pulposus cells [32], indicating that regulation of syndecan-4 expression can be mediated by the HIF-1α/β pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Soon after the identification of syndecan-1, there were some studies of its promoter [207, 208], indicating sites for Sp1 family (specifically Sp3 in more recent studies [209]), NF-kB, MyoD (Ebox) and Antennapedia [207] as well as Wilms’ tumor suppressor gene (WT1; [210]). However, syndecan-1 is not well known as an early response gene, unlike syndecan-4, where its expression has been well documented to be NF-kB and hypoxia sensitive [211, 212]. …”
Section: Syndecans and Their Roles In Breast Cancermentioning
confidence: 99%